Fitoremediasi Tanaman Jarak Pagar (Jatropha curcas) pada Tanah Tercemar Logam Berat Timbal (Pb) dari Limbah Batubara - Nia Febrianti; Muh. Ilham; Nur Aulia Hazzah; Angga Andriana; Erwing Erwing; Rizal Irfandi; Syamsu Rijal; Ruslang Ruslang (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine the effectiveness of Jatropha plant in accumulating metal contaminants in the form of lead (Pb) in coal solvent. The method used is descriptive quantitative analysis method. The results showed that the metal content of lead (Pb) in the soil before and after treatment changed from 25.8904 mg/kg to 14.3991 mg/kg. In conclusion, Jatropha curcas (Jatropha curcas) is able to accumulate the presence of metal contaminants in the form of lead (Pb) because the metal concentration in the soil decreases after the acclimatization period, so this plant species is very suitable to be used as a phytoremediation effort to reduce contaminants in heavy metal polluted soil. Keyword: Phytoremediation, Jatropha Curcas, Lead Metal (Pb)